EFFECT OF EMBLICA OFFICINALIS FRUIT DRY POWER ON BEHAVIOR CHANGES AND ANTIOXIDANT LEVELS: AN IN VITRO AND IN VIVO STUDY - UMAMAHESWARI A,; BHUVANESWARI K,; MUTHURAMAN PL, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study aim was to compare the in vitro antioxidant property of fresh juice and dry powder of Emblica officinalis (EO) by chemical testing and 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) assay and also to observe the in vivo effect of EO fruit dry powder on food intake, body weight, behavior changes, and antioxidant levels in restraint stress rat model. Methods: In vitro study, EO fresh juice 1% v/v and its dry powder form were analyzed for chemical testing and DPPH assay initially. In the in vivo study, 12 adult male Wistar rats were obtained. Initially, baseline parameters (Body wt, food intake, behavior changes, blood levels of superoxide dismutase, and malondialdehyde) and control values were assessed. Later 12 animals were divided into two treatment groups (1 and 2) and pre-treatment was given with dry powder of EO at a dose of 250 mg/kg and 500 mg/kg orally once a day, respectively. Animals from both the groups were restrained for 2 h/day and the same parameters were analyzed at the end of 24 h and 7 days of stress induction. Results: In vitro study, fresh juice and dry powder preparations of EO were found to be positive for all the four chemical testing. In DPPH assay, dry powder showed better antioxidant activity (97%) than the fresh juice form (57%). In vivo study, significant antioxidant activity was seen at the dose of 500 mg/kg after day 1 and 7 days of stress induction. Conclusion: Dry powder of EO has brought out the reversal of restraint stress-induced behavioral changes and reduced food intake, body weight, and antioxidant levels.